PENGARUH SUDUT KEMIRINGAN DRIVE PULLEY DAN PEGAS SLIDING SHEAVE RACING TERHADAP TORSI MOTOR MATIC 150 CC: THE EFFECT OF DRIVE PULLEY INCLINATION ANGLE AND RACING SLIDING SHEAVE SPRING ON TORQUE OF 150 CC MATIC MOTORCYCLE - Hidayatullah, Alfian (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2024)
There are many ways to improve the performance of an automatic motorcycle, for example by changing the tilt angle of the drive pulley and using a racing sliding sheave spring. Changing the tilt angle of the drive pulley which is varied with a racing sliding sheave spring is considered to increase the torque and power on the motorcycle so that the resulting performance feels more responsive. The purpose of this study is to determine the torque of the 2015 150 cc matic motorcycle from the effect of using a variable angle drive pulley tilt with a sliding sheave racing spring. This study uses an experimental method using a drive pulley tilt angle of 13.5 °, 13.8 °, and 14.2 ° varied spring rpm 1000, rpm 1500, rpm 2000. The use of a 13.5° drive pulley with a 1000 rpm spring produces the highest torque of 44.47 N.m at 2500 rpm. The use of drive pulley 13.8° with spring Rpm 1000 amounted to 44.41 N.m at 1500 Rpm and the use of drive pulley tilt 14.2° with spring Rpm 2000 amounted to 43.57 N.m at 1500 Rpm.